Neuroinvasive Listeriosis: Could Petechial Hemorrhages be a Diagnostic Clue?. Issue 3 (May 2018) - Diker, Sevda; Okar, Serhat; Mehdikhanova, Lale; Arsava, Ethem Murat; Kurne, Asli; Çevik, Işin Ünal; Akyön, Yakut; Alp, Şehnaz; İnkaya, Çağkan; Akova, Murat; Mut, Melike; Göçmen, Rahşan; et al.
Abstract : Introduction: Listeria monocytogenes –related central nervous system infections may involve the cerebral parenchyma. Meningitis and meningoencephalitis are the most commonly seen forms and mainly affect immunocompromised patients; however, a less frequent form, rhombencephalitis, can occur in otherwise healthy people. Early treatment with appropriate antibiotic therapy is crucial for this otherwise fatal disorder. However, it is not always possible to rapidly establish the diagnosis because of varying presentations and discrepancies in diagnostic tests. Case Report: Herein we report 3 cases of listerial infections involving the central nervous system parenchyma, with versatile diagnostic challenges and related possible solutions and radiologic hints to overcome similar issues in the future. Conclusions: We point out the importance of nonconventional magnetic resonance imaging techniques in the diagnosis, as we detected petechial hemorrhages in the brain parenchyma in all cases, which can be a diagnostic clue.